MTA matrix technique: restoration of teeth with deep subgingival defects extending down to the Osseous Crest - Mente, Johannes; Hieber, Fabian; Sekundo, Caroline; Schüßler, Dorothée L.; Gehrig, Holger (The journal of adhesive dentistry, 2022)
Purpose: To present a new restorative technique for the restoration of teeth with deep subgingival hard tissue defects extending down to the osseous crest without additional surgical or orthodontic interventions by combining mineral trioxide aggregate (MTA) and composite material.
Gesehen am 04.07.2023